Penerapan Media Pembelajaran Interaktif dalam Meningkatkan Kualitas Pembelajaran di SDN 40/II Tebing Tinggi - Ahmad Farhan Alisnaini; Ismarina Rosida; Putri Hidayati; Nurul Hikmah; Erman Har; Karmila Suryani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning in elementary schools requires innovation to ensure effective and meaningful teaching and learning. One innovation that can be implemented is the use of interactive learning media. This study aims to describe the application of interactive learning media in improving the quality of learning at SDN 40/II Tebing Tinggi. This study used a qualitative approach with a case study design. The research subjects included classroom teachers and elementary school students. Data collection techniques were carried out through in-depth interviews, learning observations, and documentation studies. Data analysis was carried out using an interactive model that includes data reduction, data presentation, and conclusion drawing. While data validity was tested through triangulation techniques. The results showed that the application of interactive learning media can increase student engagement, facilitate understanding of the material, increase learning motivation, and create more active and communicative learning interactions. However, this study also found obstacles in the form of limited facilities and teacher readiness in managing interactive media-based learning. Overall, this study concludes that interactive learning media plays an important role in improving the quality of learning in elementary schools and needs to be continuously developed as part of learning innovation